Al-Imsal al-Arabiyah Fununuha wa ilwanuha - Wardani, Yaniah (Buletin Al-Turas, 2005)
The proverb in Arabic Literature study consisted of five kinds: proverb of wisdom (al-Amsal Hikamiyah), Proverb ofÂ history (al-Amsal al-Tarikhiyah), Proverb of the nation (al-Amsal al-Syababiyah), Proverb of mistic (al-Amsal al-Fukahiyah). These proverbs above widely developed in the eraÂ of Jahiliyah and the first Islamic period. They also played a very important role in improving the Arabic literature.